1990
DOI: 10.1038/346719a0
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of p21ras upon T-cell activation

Abstract: External signals that control the activity of proteins encoded by the ras proto-oncogenes have not previously been characterized. It is now shown that stimulation of the antigen receptor of T lymphocytes causes a rapid activation of p21ras. The mechanism seems to involve a decrease in the activity of GAP, the GTPase-activating protein, on stimulation of protein kinase C. In lymphocytes, p21ras may therefore be an important mediator of the action of protein kinase C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
553
5
1

Year Published

1993
1993
2000
2000

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 865 publications
(580 citation statements)
references
References 20 publications
20
553
5
1
Order By: Relevance
“…Activation of protein kinase C downstream of PLCg could contribute to activation of MAP kinase through protein kinase C phosphorylation of Raf (SoÈ zeri et al, 1992). Alternatively, a protein kinase C pathway could contribute to the activation of Ras itself: while this has been reported previously in lymphocytes (Downward et al, 1990), in most cell types PKC activation is not su cient to cause Ras activation. However, in PC12 cells activation of PKC by phorbol esters has been shown to result in elevation of GTP levels bound to Ras (Nakafuku et al, 1992).…”
Section: Discussionmentioning
confidence: 80%
“…Activation of protein kinase C downstream of PLCg could contribute to activation of MAP kinase through protein kinase C phosphorylation of Raf (SoÈ zeri et al, 1992). Alternatively, a protein kinase C pathway could contribute to the activation of Ras itself: while this has been reported previously in lymphocytes (Downward et al, 1990), in most cell types PKC activation is not su cient to cause Ras activation. However, in PC12 cells activation of PKC by phorbol esters has been shown to result in elevation of GTP levels bound to Ras (Nakafuku et al, 1992).…”
Section: Discussionmentioning
confidence: 80%
“…This e ect could be a result of either increased guanine nucleotide exchange or a decrease in RasGAP activity, an e ect previously documented in T-cells (Downward et al, 1990). Several reports have detailed the use of the RasN17 dominant negative mutant to demonstrate the Ras-independence of phorbol ester-dependent Raf regulation (Arai and Escobedo, 1996;Zou et al, 1996).…”
Section: Discussionmentioning
confidence: 87%
“…This observation is not unique to C3H10T1/2 ®broblasts since Downward et al (1990) observed that T-lymphocytes contained little, if any, c-Ha-ras protein. C3H10T1/2 cells are readily transformed by the ectopic expression of either activated (G12V)Ha-ras (V12H10 cells) or (Q61K)Nras (K61N10 cells), as characterized by the acquisition of a refractile cell morphology and the ability to form foci in soft agar (data not shown).…”
Section: Expression Of Activated Ras In C3h10t1/2 ®Broblastsmentioning
confidence: 91%